Hubungan Pengetahuan Komunikasi Terapeutik terhadap Kemampuan Komunikasi Perawata dalam Melaksanakan Asuhan Keperawatan di Rumah Sakit Elisabeth Purwokerto - Diana RS,; Asrin,; Ekowati, Wahyu (Jurusan Keperawatan FIKES UNSOED, 2006)
Therapeutic communication is very important to construct the therapeutic relation of nursepatient and influences the improvement of quality of treatment service. Success of terapeutik communication is influenced by some factors such as lack of nurse's knowledge and ability to apply the therapeutic communication. The purpose of this study was to know the relationship between knowledge of therapeutic communication towards the nurse's communication ability in implementing the treatment upbringing in Elisabeth Hospital Purwokerto. The descriptive Research type of correlation. Population research is all nurses in Maria lodge of Elisabeth Hospital Purwokerto in the amount of 26 people, The research sample is taken from 23 people in according to the inclusive criteria. Data analysis method uses the distribution of frequency and statistic test